Determinan Keputusan Pembelian Pengguna E-Commerce Tiktok Shop: Digital Marketing, Fitur Live Streaming, Online Customer Review, Content Marketing - Komsi Koranti; Syntha Noviyana; Sriyanto; Nila Anjar Ramadhona (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
Current technological developments are in line with the increasing number of internet users. Internet users make it easier for people to meet their needs, such as online shopping. The purpose of this study was to analyze the influence of digital marketing, live streaming features, online customer reviews, content marketing on purchasing decisions and to determine the independent variables that have the most dominant influence on purchasing decisions on the Tik Tok Shop e-commerce application. This research method uses primary data with the test stages carried out, namely validity, reliability, normality, heteroscedasticity, multicollinearity, multiple linear regression, F test, t test and coefficient of determination. Data collection was carried out using a questionnaire instrument with data collected from 100 respondents. The sampling method in this study is non-probability sampling with a purposive sampling technique. The testing tool used is SPSS. The results of the study showed that purchasing decisions were simultaneously influenced by digital marketing variables, live streaming features, online customer reviews, content marketing. Purchasing decisions were partially influenced by live streaming features, online customer reviews, and content marketing. digital marketing did not have a significant influence on purchasing decisions. Content marketing is the variable that has the strongest influence on purchasing decisions.